Mangrove seeding technology application for rehabilitation and optimization program of coastal area to be an ecotourism area in Belawan Sicanang (Talenta Publisher, 2019)
Most of the mangrove ecosystems in North Sumatera have changed the statue into the lands of business which is ignoring environmental aspects. Such as pond clearing, conversion of land into plantations and agriculture, etc. The most ironic happens on Belawan Sicanang, Medan Belawan, Medan City. This has caused fundamental changes for mangrove ecosystem Belawan Sicanang is the only one subdistrict in Medan City which has the widest mangrove ecosystems, i.e. 895.24 ha. However, in recent years has been both quality and quantity declines in mangrove ecosystems due to land conversion into the industry, habitation, ponds, and palm plantation. This mangrove ecosystem has an important function as a buffer zone of Medan city from tidal floods, abrasion, strong waves, and tsunami. Moreover, mangrove ecosystems also functionate as a place for the reproduction of seawater biota which is the source of small fisherman livelihood living in the coastal area. The application of mangrove wood-seeding technology is a solution for wood-mangrove regeneration and rehabilitation which is very useful for mangrove habitat. Inventory of mangrove seedlings is important for mangrove rehabilitation activity. Seedling sources used are comes from the local area so that is expected for facilitating in seed collection and makes the living percentage of mangrove seeds higher. Through a dedication activity, enthusiasm appeared and a citizen or partner group interested in participating in dedication activity so that is expected to foster enthusiasm in protecting the coastal environment by conducting seedings and rehabilitation of mangrove forests. Then, the mangrove condition caring community of Belawan Sicanang, Medan Belawan, Medan City formatted, so that the target to make coastal area became ecotourism area optimized.